(untitled) (International Journal of Engineering and Computer Science, 2018)
Wireless Sensor Networks (WSNs) have concerned much attention in recent years. The prospective applications of WSNs are enormous. They are used for collecting, storing and sharing sensed data. WSNs have been used for various applications including habitat monitoring, agriculture, nuclear reactor control, security and tactical surveillance. The WSN system developed in this project is for use in precision agriculture applications, where real time data of climatological and other environmental properties are sensed and control decisions are taken based on it to modify them. The architecture of a WSN system comprises of a set of sensor nodes and a base station that communicate with each other and gather local information to make global decisions about the physical environment. Farmers depend heavily on the rains because they lack the access to irrigation facilities. Their crop yields are highly unreliable due to the variability in both rainfall amount and its distribution. Also these farmers depend heavily on the prediction values of various factors such as weather, water, soil, etc. Agriculture faces many challenges, such as climate change, water shortages, labour shortages due to an aging urbanized population, and increased societal concern about issues such as animal welfare, food safety, and environmental impact. Sensor network and other agricultural techniques might help them to store and utilize the rain water, increase their crop productivity, reduce the cost for cultivation and make use of real time values instead of depending just on prediction.